Biosorption of lead (II) from an aqueous solution using biosorbents prepared from water plants - E, Tseveendorj; T, Enkhdul; Lin, S; D, Dorj; Sh, Oyungerel; T.O, Soyol-Erdene (Mongolian Journal of Chemistry, 2018)
Due to its toxicity causing serious health problems, persistence in the environment and non-biodegradability, lead (Pb) is considered as one of the most harmful metals on earth. In this study, dried aquatic plants as sorbents including Nymphoides peltata (NP), Typha laxmannii (TL), and Eichhornia crassipes (EC) were examined and compared to discover the best biosorption for Pb. The effect of physical and chemical parameters including pH (2.0–5.5), sorbent dosage (1–5 g/l), metal concentration (20–100 mg/l), and contact time ( 240 min) were investigated to determine the optimal condition for Pb(II) biosorption. As a result, the optimum pH, sorbent dosage, and contact time were 5.0, 1 g/l, and 120 minutes, respectively. Pb2+ biosorption data were found to follow the Langmuir isotherm model while the kinetic biosorption data followed pseudo-second-order model. The maximum biosorption capacity from Langmuir model was calculated as 63.3, 82.9, and 51.9 mg/g for EC, NP, and TL, respectively. All the results showed that biosorption efficiencies of Pb(II) by different biosorbents were in following order NP>EC>TL.